'I played by all the rules! Why didn't you tell me there weren't any rules, it's not fair!':contradiction, corporeality, and conformity in Grace and Frankie1. Issue 6 (2nd November 2021) - Fiedler, Amanda; Casey, Sarah
ABSTRACT: 1 Netflix show, Grace and Frankie, is significant in its representation of ageing. While it may appear ground-breaking to see people in their seventies and eighties navigating (re)invention of self and sexuality within mainstream media, upon closer inspection–in particular, Season Four–the inherent contradictions common to postfeminist texts are exposed. Initial offerings from G race and Frankie extend to positive representations of ageing sexuality, female agency, and self-efficacy; however, these themes are rather negated as the seasons progress. Such incongruities feature notions of what might be considered as effective ageing: a dualism in which ageing femininity is both celebrated and fought; discourses of empowerment via rigorous, yet relatively ineffective, corporeal self-maintenance/somatic discipline; a sexualised 'feminism' which also features the women as variously alone, but dependent upon their ex-husbands, each other, or their children; and a postfeminist 'makeover' paradigm in which the pendulum swings between preservation and restoration, individualism and conformity. Albeit within neoliberal and postfeminist discourses, Grace and Frankie, while flawed, remains an important text in which visibly ageing bodies, ageing sexuality, and non-normative identification are elevated and explored.